Divergences in EMU: Scope of the problem and policy options - Sebastian Dullien (Intervention. European Journal of Economics and Economic Policies, 2009)
First paragraph: Ten years after the introduction of the euro, the question of economic divergence has gained new prominence. While immediately after the introduction of the euro, skeptical voices about the young currency's sustainability fell silent, the debate first reemerged in the years after the bursting of the New-Economy-bubble in 2000. With Italy and Germany underperforming the rest of the euro-area in the recovery after 2001, think-tanks and investment banks debated whether economic divergence might in the end lead to a break-up of the currency union (Gros 2006, Munchau 2006, Prior-Wandesforde/Hacche 2005).
Keywords: 330